“Even more than that, men love cars”: “Car guy” memes and hegemonic masculinity - Dundes, Lauren (Frontiers in Sociology, 2023)
ABSTRACT The construction of gender identities occurs through a variety social forces, including memes widely circulated on social media. Beyond the function of internet memes as entertainment, they also promote gender-based bonding through humor in ways that encourage performative gender roles central to self-image. Decoding memes as a form of contemporary data reveals desires and fears, both conscious and unconscious, that underlie dramaturgical performances supporting hegemonic masculinity. In the case of “car guys”, car afficionados whose passion for cars is integral to their identity, memes reflect the group’s aspirational presentation of self, including cars as a symbolic physical embodiment of hegemonic masculinity. This semiotic study of 60 car guy memes shared on social media uncovered recurrent motifs centered around cars’ ability to affirm men’s position in the metaphorical driver’s seat. Flashy cars were often portrayed as more desirable than women, a sentiment encapsulated by the meme, “Men love women, but even more than that, men love cars”. This novel analysis of memes explores the ostensible male preference for fantasy cars over emotionally-risky relationships. Two salient themes relevant to conceptions of masculinity emerged: 1) car guys’ apprehensions about male-female interdependence and 2) frustration with women’s discretion in meeting men’s emotional and sexual needs. Memes as a cross-sectional, unfiltered data source provide insight into the need to reconcile car culture with gender equality.